Public Policy of Silencing: a Possible Concept? (Clepsidra - Interdisciplinary Journal of Memory Studies, 2022)
The Brazilian process of reckoning with its authoritarian past in the post-dictatorship period was marked by a conservative perspective of “turning the page”. In this context this paper present a public policy of silencing was constituted and intentionally damaged the agendas of memory, truth, and justice through four elements: privatization of memory, ideology of reconciliation, silencing of those affected, and veto power of the military. Finally, despite having gone through a period of advancement of memory policies (2007-2014), the country is currently facing the return of silencing under its most severe version, at risk of complete exclusion.
Keywords: Public policy of silencing; memory; transitional justice; Brazilian military dictatorship